NLRP3-mediated pyroptosis in diabetic nephropathy - Wan, Jiayi; Liu, Dongwei; Pan, Shaokang; Zhou, Sijie; Liu, Zhangsuo (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is the main cause of end-stage renal disease (ESRD), which is characterized by a series of abnormal changes such as glomerulosclerosis, podocyte loss, renal tubular atrophy and excessive deposition of extracellular matrix. Simultaneously, the occurrence of inflammatory reaction promotes the aggravation of DN-induced kidney injury. One of the most typical changes in pyroptosis is the activation of inflammasome and the formation of membrane pores dependent on gasdermin family. Converging studies shows that pyroptosis can occur in renal intrinsic cells and participate in the development of DN, and its activation mechanism involves a variety of signaling pathways. In addition, a number of drugs targeting pyroptosis-associated proteins have been shown to have potential for treating DN. In this review, the pathogenesis of pyroptosis and several possible activation pathways in DN were reviewed, and some drugs used to treat pyroptosis were summarized. Although relevant studies are still not thorough and comprehensive, these findings still have certain reference value for the understanding, treatment and prognosis of DN.